Young Generation Point of View About Non-Fungible Token as a Future Currency and Assets - Silalahi Pretty Mona Jessie; Buhara Tiara; Hendratno Setiani Putri (E3S Web of Conferences, 2023)
This research focuses on how artists and the young generation perceive the use of NFT and their impact on the future value of currencies. It increases the author’s curiosity about the reactions of artists and the young generation to the use of NFT and its impact on future currencies. The authors also wanted to know why they are publishing digital works on NFT and whether they think NFT is the future of digital assets researchers or just a bubble. This study uses a qualitative method with semi-structured interviews with artists and the younger generation with the criteria of understanding and using NFT, understanding and not using NFT, and not understanding and not using NFT. The result that the authors get from this research is that the use of NFT has been widely used by artists and the younger generation. They say that the publication of digital works can be guaranteed. Another interesting thing is that they consider NFT to have a great opportunity as an asset in the future, where the use of cryptocurrency also affects the value of the currency in the future. However, the younger generation is not interested in NFT. They prefer NFT to be implemented as a payment system in the future.